Exogenous Lipid Pneumonia Related to Smoking Weed Oil Following Cadaveric Renal Transplantation - Dilini Vethanayagam; Stewart Pugsley; EJ Dunn; David Russell; J Michael Kay; Christopher Allen (Canadian Respiratory Journal)
A 30-year-old female presented shortly after cadaveric renal transplantation with respiratory distress typical of a bacterial infection. Following initial improvement, she developed progressive respiratory failure, initially felt to be secondary to cytomegalovirus infection. Two bronchoalveolar lavages were nondiagnostic, and an open lung biopsy was performed, which revealed a pulmonary alveolar proteinosis (PAP) reaction and exogenous lipid pneumonia (ELP). The ELP was considered to be secondary to the use of marijuana, in the form of weed oil, that was smoked daily for over 10 years and stopped just before renal transplantation. This is the first description of both PAP and ELP following renal transplantation, and the first description of ELP related to smoking weed oil. Physicians should be aware of the different forms of marijuana available and of their potential medical complications.